Visceral Leishmaniasis and Herpes Zoster as a Component of Syndrome of Immune Reconstitution Inflammatory Syndrome in an HIV-Positive Patient - Ermira Muço; Arta Karruli; Neada Hoxha; Alma Hoxhaj; Majlinda Kokici (Case Reports in Infectious Diseases)
Immune reconstitution syndrome (IRIS) is a state of unusual hyperinflammatory response against latent infections which occurs after CD4 cell count improvement and as a consequence of immune response once highly active antiretroviral therapy for HIV is introduced. Leishmania parasites and varicella zoster virus (VZV) may be a manifestation of IRIS, but few data exist in literature in particular regarding Leishmania parasites. Case Presentation. A 47-year-old man was admitted to our hospital with fever. He was diagnosed with HIV infection and was a late presenter according to CD4+ count of 98 cells/mm3/9.5% and baseline illness (chronic diarrhea, weight loss, and oral candidiasis). The patient started highly active antiretroviral therapy (abacavir plus lamivudine plus efavirenz). Clinical symptoms improved and CD4+ increased to 22%, 374 cells/mm3. After 88 days, he presented with a 17-day history of high fever, sweat, fatigue, further weight loss, and lethargy. According to clinical image findings and hematochemical parameters, the patient was diagnosed with visceral leishmaniasis. He improved under treatment with liposomal amphotericin B. He presented again, 105 days after with disseminated herpes zoster infection. CD4+ count was 28.5%, 455 cell/mm3. The patient started treatment with acyclovir for 10 days. Four weeks later, he had no skin elements. At present, the patient continues HAART and is under regular monitoring. Conclusions. Early diagnosis of IRIS-associated diseases and treatment were fundamental in the patient’s prognosis. Our patient presented with two different components of IRIS in two different time frames, confirming IRIS to be a broad-spectrum disease, heterogeneous and unique for each patient. A close monitoring during ART initiation, in particular in late presenters, is important in preventing IRIS. In case of IRIS development, a detailed investigation of rare associated diseases not only common ones is of great importance for the management and the prognosis of these patients.